A Comparison of Outcomes in Patients with Infrapopliteal Disease Randomised to Vein Bypass or Plain Balloon Angioplasty in the Bypass vs. Angioplasty in Severe Ischaemia of the Leg (BASIL) Trial. (August 2017) - Popplewell, M.A.; Davies, H.O.B.; Narayanswami, J.; Renton, M.; Sharp, A.; Bate, G.; Patel, S.; Deeks, J.; Bradbury, A.W.
Abstract : Objective: The aim was to compare outcomes in a subgroup of patients with infrapopliteal (IP) disease randomised to infrapopliteal vein bypass (VB) or plain balloon angioplasty (PBA) in the original BASIL trial. Methods: A comparison of outcomes from patients randomised to VB or PBA undergoing revascularisation for severe limb ischaemia (SLI) because of IP disease with or without femoropopliteal disease. Data were extracted from case report forms from the BASIL trial. The primary outcome was amputation free survival (AFS); secondary outcomes included overall survival (OS), 30 day mortality and morbidity, freedom from arterial re-intervention, immediate technical success, repeat and crossover interventions, length of hospital stay, and quality of revascularisation. Results: A total of 104 patients were identified in the BASIL study with IP disease, 56 randomised to IP VB, and 48 to IP PBA. Groups were similar at baseline except for more chronic kidney disease and non-steroidal anti-inflammatory drug use in the VB group, and more previous surgical arterial intervention and antihypertensive use in the PBA group. There were no statistically significant differences in AFS or OS; however, clinically important trends were apparent in favour of a VB first strategy. Patients allocated to VB demonstrated significantly quicker relief of rest pain when compared with PBA ( p =  .005), but no significant differences in improved tissue healing. Median length of index hospital admission was significantly greater in the VB than in the PBA group (18 vs. 10 days, p  < .0001) but there was no difference between the two groups in median total hospital stay between randomisation and the primary endpoint (VB 43.5 vs. PBA 42 days). Conclusions: Further randomised trials, like BASIL-2 and BEST-CLI, are required to determine whether patients with severe limb ischaemia who require IP revascularisation and who are suitable for VB should have bypass or endovascular intervention as their primary revascularisation procedure.